Probiotics, prebiotics, synbiotics in prevention and treatment of inflammatory bowel diseases - Tanja Petreska Ivanovska; Maja Jurhar Pavlova; Kristina Mladenovska; Lidija Petrushevska-Tozi (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2014)
Probiotics, prebiotics, and synbiotics are functional components able to exert positive effects on human health. Numerous medical conditions lack effective and safe approaches for prevention or treatment, thus usage of probiotics, prebiotics, and synbiotics is an alternative. Further, the benefit related to the consumption of these compounds is associated with lower morbidity of chronic diseases and reduced health-care costs. Various types of mediums to deliver probiotics/synbiotics to the human GIT are used. Although capsules and tablets are frequently applied as delivery systems for probiotics, the major challenge of the commercial sector is to market new functional foods containing probiotics and/or prebiotics. Discovering of new probiotic/synbiotic functional foods is connected to the interest of the food industry to revitalize continuously through introduction of products with improved nutritional value and pleasant taste, but also with health benefit for the consumers. The review provides insights and new perspectives in respect to usage of functional components and foods in prevention and treatment of inflammatory bowel diseases (IBD) that are highly correlated with the modern lifestyle. The therapeutic and safety properties of probiotics and prebiotics, their role in pathogenesis of IBD, potential to prevent and treat these diseases as well as postulated mechanisms of action will be discussed, highlighting the main areas in which further research is an emergence.